Mixed-Type Melasma Treated with Low Fluence Q-Switched Nd-YAG 1064 nm Laser: A Case Report - Nugrahani, Aninda Fitri; Murlistyarini, Sinta (Indonesian Journal of Medicine, 2020)
Background: Melasma is an acquired, chronic hypermelanosis condition. Melasma is more common in women of all races and occur especially on the face. The pathogenesis of melasma is very complex and the treatment is still a challenge. The purpose of this study was to report mixed-type melasma treated with low fluence Q-switched Nd-YAG 1064 nm laser.Case Presentation: A case of melasma in 54 year old woman was reported. Dermatological examination showed presence of brownish macules and patches in the centro facial area with symmetrical distribution. Examination with wood lamp showed mixed type. Patients have received topical therapy but there were no improvement.Results: The patient was then treated with low fluence Q-switched Nd-YAG 1064 nm laser for three sessions with an interval of 2 weeks. At 6 weeks of treatment the modified MASI (mMASI) value was reduced from 8.4 to 4.6 and the VAS value was increased from 2 to 8.Conclusion: The depth of the pigment determined the response to therapy. In the mixed type melasma the response for therapy is only partial. The low-fluence Q-switched Nd-YAG 1064 nm laser can penetrate deeper into the dermis and damage melanin in a short time.Keywords: mixed typed melasma, low fluence, Q-switched Nd-YAG laserCorrespondence: Aninda Fitri Nugrahani. Department of Dermatology and Venereology, DR. Saiful Anwar Hospital, Malang, East Java/ Faculty of Medicine, Universitas Brawijaya, Malang, East Java. Email: aninda16fitri@gmail.comIndonesian Journal of Medicine (2020), 05(02): 95-101https://doi.org/10.26911/theijmed.2020.05.02.01